Shopping for Health: Herbs and Spices - Jenna A. Norris; Wendy Dahl (EDIS)
Herbs and spices have been used for hundreds of years in cooking and medicine. They add a wide range of flavors to food and may also provide health benefits. For some people, using herbs and spices in cooking may be a challenge, but it doesn’t have to be that way! The information below will get you on track to enjoying zesty, flavorful, healthy cooking. This 4-page fact sheet was written by Jenna A. Norris and Wendy Dahl and published by the UF Department of Food Science and Human Nutrition, April 2013.